사전 기술을 위한 통속어의 개념과 유형 - 안의정(Ahn, Euijeong); 김현강(Kim, Hyun-Kang); 손희연(Son, Hui-Youn) (한국사전학, 2013)
This study is aimed at exploring how the dictionary could describe the extensive phenomenon and various types of vernacular in detail, based on discussion on the concept of vernaculars. Such study starts with the idea that discussing the concept of ‘vernacular’ is a prerequisite of recognizing the value of everyday language, and identifying and describing its nature and phenomenons associated with it. First of all, this study confirmed the innate secularity and dailiness of everyday language and established the concept of vernacular. Historically, the process of individual languages including Korean being conceptualized demonstrated that ‘noble language’ separate from everyday communications become secularized,and such language turns into everyday language and norms, which is ironical and universal. Vernaculars are the result of such universal phenomenon involving secular, everyday language, showing various aspects and functions, based on secular effects, popularity and the nature of colloquial language. Based on such concept and nature of vernaculars, this study tried to explore ways of describing them in dictionaries, on the premise that vernaculars are an universal phenomenon as an everyday language. To achieve the goal, this study defined the phenomenon of vernaculars in terms of linguistic forms and various types of vernaculars for dictionary definition. Next, the method of describing diverse words and language phenomenons associated with ‘vernaculars’ in detail in dictionaries was discussed. Given the characteristics of vernaculars, they cannot be limited to words, which means phrases or sentences and non-segmental units should also be included in the description of vernaculars. In addition, since they have functional properties beyond the lexical meanings, relevant situations, nuances and causes of their occurrence should be described in detail, and separate register labels and metalanguages are needed for description of the environment and uses of vernaculars. KCI Citation Count: 3